Coronary Artery Bypass Graft in a Young Adult, An Emerging Phenomenon: A Case Report - ARM, Ramzisham; OSM, Joanna; AR, Talal; S, Shahrulakmal; O, Maskon; S, Noorfaizan; DM, Zamrin (IIUM Medical Journal Malaysia, 2010)
A 29-year-old, smoker, diabetic, hypertensive and hypercholesterolemic man was diagnosed of having severe coronary artery disease with a critical left main stem stenosis. On-pump coronary artery bypass graft surgery (CABG) was performed using conduits from the left internal mammary artery as well as the left radial artery and right saphenous vein which were both harvested endoscopically. He was discharged after a week of uneventful recovery. This case emphasizes on the best possible management of conduits selection, intraoperative myocardial protection and the risk factors modification in achieving a long term graft patency and avoiding premature cardiac related death.